Harmonisasi Nilai Pendidikan Islam dengan Tradisi Balai Hakey dan Tetek Pantan: Kajian Etnopedagogi Suku Dayak Ma’anyan di Kalimantan Tengah - Hamdi; Normuslim; Muslimah (Kartika: Jurnal Studi Keislaman, 2025)
The phenomenon of Muslim participation in Hindu Kaharingan religious rituals in Central Kalimantan reflects a compelling form of cultural interaction and acculturation between Islamic values and the local traditions of the Dayak Ma’anyan community. This study employs a qualitative ethnographic approach to explore the harmonization of Islamic educational values with the traditions of Balai Hakey and Tetek Pantan through an ethnopedagogical perspective. Data were collected through in-depth interviews, participant observation, and documentation conducted in East Barito Regency. The findings reveal that Balai Hakey embodies values of togetherness, leadership, and tolerance, while Tetek Pantan represents values of gratitude, morality, and collaboration. Both traditions foster mutual respect, a strong work ethic, and social responsibility within the community. The harmony between Islamic values and local wisdom demonstrates a contextual and culturally responsive model of character education that is relevant to multicultural societies. The integration of these values not only strengthens character education but also contributes to the preservation of Dayak Ma’anyan cultural heritage